The impact of polymer mixture composition on the properties of electrospun membranes for drug delivery applications - Švára, Dominik; Filipová, Barbora; Jelínek, Petr; Mikeš, Petr; Kluk, Anna; Šoóš, Miroslav (International journal of pharmaceutics, 2023)
Orally dispersible films (ODFs) prepared by an electrospinning are a novel type of pharmaceutical formulation. This dosage form has the potential to be beneficial for small children and the elderly, who can have problems with administration of classical tablets due to the increased risk of choking and difficulty with swallowing. Due to the highly porous nanofiber morphology, the ODFs examined in this study achieve rapid disintegration into drug microparticles when in contact with saliva. The suspension is then easier to swallow. In this study, we focus on the impact of film composition (polymer matrix composition) on the properties of electrospun membranes. In particular, we prepared ODFs composed of a mixture of PEG 100 000 with HPMC E5 and PVP k90 with HPMC E5. We found significant differences in the structure of electrospinned membranes, where samples containing PEG 100 000 and HPMC E5 exhibited much narrower distribution of fibers. Furthermore, nanofibers containing PVP k90 exhibit a faster disintegration rate, while dissolution of the drug was faster in the case of PEG 100 000 containing ODFs. The improvement was caused by both the structure and composition of the membranes.
Keywords: polymery; příprava léků; Child; Polymers; lidé; lékové transportní systémy; senioři; Drug Delivery Systems; Drug Compounding; dítě; Aged; Tablets; Solubility; tablety; rozpustnost; Humans